Auxetic cell structure as an impact absorbing material in bio-composite aero helmet - Yaakob, Mohd Saffuan (2016)
This study is specifically concerned with the application of auxetic cell structures as an impact absorbing material. Despite the need of high energy absorption materials in safety application, limited research has been devoted to identify the potential of auxetic cell structures as an impact absorbing materials. An extensive literature review highlighted past research on auxetic cell structure and its limitation, especially as related to energy absorbed, fabrication process and application. The information gaps identified in the review became the basis of this study in creating an impact absorbing materials for bio-composite aero helmet interior. The main objective of this research is to design a new interior for bio-composite aero helmet comply to standards set by The Consumer Product Safety Commission of bike helmet standard. Experiments were conducted namely drop weight impact test and oblique impact test. The study follows ASTM D7136 / D7136M – 15 standards and European Standard; EN 1078. Comparison has been made between the Expanded Polystyrene (EPS), Polyurethane Foam, Auxetic Design 1 and Auxetic Design 2 to evaluate the energy absorbed in drop weight impact test. Experimental results showed that Auxetic Design 2 and Polyurethane Foam has shown a high absorbed energy thus been used as material for helmet interior. For oblique impact test, four sport cycling helmets being tested; Kabuto Helmet, Kenaf Helmet, Flax Helmet and Flax Helmet with Auxetic Interior. The study proved that flax helmet with auxetic interior has the lowest linear acceleration compared to other helmets tested. When used as interior materials, auxetic cell structure can potentially improve the safety factor in bio-composite aero helmet. Main findings revealed that auxetic cell structure proved to be the best alternative impact absorbing material compared to crushable foam, as helmet interior.